Post-authorisation passive enhanced safety surveillance of seasonal influenza vaccines: protocol of a pilot study in England. Issue 5 (17th May 2017) - de Lusignan, Simon; Dos Santos, Gaël; Correa, Ana; Haguinet, François; Yonova, Ivelina; Lair, Florence; Byford, Rachel; Ferreira, Filipa; Stuttard, Karen; Chan, Tom
Abstract : Aim: To pilot enhanced safety surveillance of seasonal influenza vaccine meeting the European Medicines Agency (EMA) requirement to rapidly detect a significant increase in the frequency or severity of adverse events of interest (AEIs), which may indicate risk from the new season's vaccine. Study design: A prospective passive enhanced safety surveillance combining data collection from adverse drug reaction (ADR) cards with automated collection of pseudonymised routinely collected electronic health record (EHR) data. This study builds on a feasibility study carried out at the start of the 2015/2016 influenza season. We will report influenza vaccine exposure and any AEIs reported via ADR card or recorded directly into the EHR, from the commencement of influenza vaccination and ends as specified by EMA (30 November 2016). Setting: Ten volunteer English general practices, primarily using the GSK influenza vaccines. They had selected this vaccine in advance of the study. Participants: People who receive a seasonal influenza vaccine, in each age group defined in EMA interim guidance: 6 months to 5 years, 6–12 years, 13–17 years, 18–65 years and >65 years. Outcome measures: The primary outcome measure is the rate of AEIs occurring within 7 days postvaccination, using passive surveillance of general practitioner (GP) EHR systems enhanced by a card-based ADR reporting system. Extracted data will be presented overall by brand (Fluarix Tetra vs others), by age strata and risk groups. The secondary outcome measure is the vaccine uptake among the subjects registered in the enrolled general practices. Ethics and dissemination: Ethical approval was granted by the Proportionate Review Sub-committee of the North East—Newcastle & North Tyneside 2 on 5 August 2016. The study received approval from the Health Research Authority on 1 September 2016. We will produce an interim analysis within 8 weeks, and an end-of-study report, which will be submitted to peer-reviewed journals.